Effect of 4-benzylidenamino-5-phenyl-4Н-1,2,4-triazole-3-thiones and salts of 2-(4-amino-5-phenyl-4Н-1,2,4-triazole-3-ylthio)acetic acid on central component of nociceptive system - Ye. S. Pruhlo (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. To study the effect of 4-benzylideneamino-5-phenyl-4H-1,2,4-triazole-3-thiones and salts of 2-(4-amino-5-phenyl-4H-1,2,4-triazole-3-yltio)acetic acid on central component of nociceptive system on condition of thermal stimulation of limbs of rats, and also to explore patterns related with the chemical structure and pharmacological activity of 1,2,4-triazole derivatives.